2022
DOI: 10.1021/acsnano.2c08411
|View full text |Cite
|
Sign up to set email alerts
|

Big Data in a Nano World: A Review on Computational, Data-Driven Design of Nanomaterials Structures, Properties, and Synthesis

Abstract: The recent rise of computational, data-driven research has significant potential to accelerate materials discovery. Automated workflows and materials databases are being rapidly developed, contributing to high-throughput data of bulk materials that are growing in quantity and complexity, allowing for correlation between structural−chemical features and functional properties. In contrast, computational datadriven approaches are still relatively rare for nanomaterials discovery due to the rapid scaling of comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 258 publications
0
12
0
Order By: Relevance
“…Several studies have already shown that data-driven approaches can be used to efficiently predict the band gap of a variety of materials. 79–83…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have already shown that data-driven approaches can be used to efficiently predict the band gap of a variety of materials. 79–83…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have already shown that data-driven approaches can be used to efficiently predict the band gap of a variety of materials. [79][80][81][82][83] After training the ML models, they are then used to make predictions on the entire space of A i A ii B 4 X 8 materials containing 12,360 structures that are not included in the original dataset of 240 structures used for DFT calculations. Next, we apply the following three filters on the materials in the resulting dataset: (i) formation energy (E f ) o 0 eV, (ii) magnetic moment (m) 4 4.55 m B , and (iii) band gap (E g ) 4 0 eV.…”
Section: Models For High-throughput Screeningmentioning
confidence: 99%
“…Data-driven research has received wide attention in the scientific community and has great potential in improving the design of materials. This study serves as a proof-of-concept for applying a meta-analytical approach to synthesize pre-existing data to determine patterns and make predictions, thereby obtaining a better understanding of the property–aggregation relationships of nanomaterials, which will be required for the development of accurate predictive models to estimate nanomaterial aggregation. This meta-analysis focused on carbon nanomaterials, and future analysis can include more types of nanomaterials (e.g., metal nanoparticles and nanoplastics) to evaluate the generalizability of the findings in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many reports have been published on predicting chemical reactions using various methods [15][16][17][18][19][20][21][22][23][24][25][26]. Even in polymer science, efforts to predict polymer properties are still being explored, as published in various reports on computational approaches [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%